Dynamic factor models - Jörg Breitung; Sandra Eickmeier (Deutsche Bundesbank, 2005)
Factor models can cope with many variables without running into scarce degrees of freedom problems often faced in a regression-based analysis. In this article we review recent work on dynamic factor models that have become popular in macroeconomic policy analysis and forecasting. By means of an empirical application we demonstrate that these models turn out to be useful in investigating macroeconomic problems.
Keywords: C13; C33; C51; 330; Principal components; dynamic factors; forecasting; Dynamisches Modell; Faktorenanalyse; Zeitreihenanalyse; Prognoseverfahren; Theorie; Schätzung; EU-Staaten